2019
DOI: 10.12659/msm.915146
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo Biloba Extract Inhibits Metastasis and ERK/Nuclear Factor kappa B (NF-κB) Signaling Pathway in Gastric Cancer

Abstract: BackgroundGinkgo biloba extract (EGb761), a standard extract of the Chinese traditional medicine Ginkgo biloba, plays an anti-tumor role in various cancers. However, whether EGb761 is involved in the invasion and metastasis of gastric cancer remains unclear.Material/MethodsIn the current study, cell viability assay, Western blotting, wound-healing assay, Transwell invasion assay, and orthotopic transplantation model were performed to explore the effects of EGb761 on gastric cancer.ResultsIn vitro, the results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 29 publications
(31 reference statements)
1
20
0
Order By: Relevance
“…As one of the most universally used herbal medicinal product [37], GBE has a wide range of pharmacological properties. Numerous studies have shown that GBE has the characters of in ammation reduction, free radical scavenging, anti-tumor and nervous system activity enhancement [19,38,39]. It is well known that the liver I/R injury generally accompanies with apoptosis, accumulation of proin ammatory cells, and ROS generation [3].…”
Section: Discussionmentioning
confidence: 99%
“…As one of the most universally used herbal medicinal product [37], GBE has a wide range of pharmacological properties. Numerous studies have shown that GBE has the characters of in ammation reduction, free radical scavenging, anti-tumor and nervous system activity enhancement [19,38,39]. It is well known that the liver I/R injury generally accompanies with apoptosis, accumulation of proin ammatory cells, and ROS generation [3].…”
Section: Discussionmentioning
confidence: 99%
“…3,4 In recent years, the anti-tumor effects of Chinese medicine monomer components have become a research hotspot at home and abroad. For example, Ginkgo Biloba extract can effectively inhibit metastasis in Gastric Cancer, 5 and Oxymatrine can strengthen the inhibitory effect of bevacizumab on breast cancer. 6 The root of Averrhoa carambola L., which is used as a folk herbal medicine, can lower blood sugar and blood lipids.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the liver I/R injury generally accompanies with apoptosis, in ammation, and ROS generation [3]. Numerous studies have shown that GBE has the characters of in ammation reduction, free radical scavenging, anti-tumor and nervous system activity enhancement [19,38,39]. GBDP is a unique and popular GBE preparation in China produced according to the Pharmacopoeia of the People's Republic of China (Edition 2015).…”
Section: Discussionmentioning
confidence: 99%